2021
DOI: 10.2319/092620-820.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the gingival thickness and keratinized gingival width of maxillary and mandibular anterior teeth after orthodontic treatment

Abstract: Objectives To evaluate changes in the gingival thickness (GT) and keratinized gingival width (KGW) of the maxillary and mandibular central and lateral incisors and canines after fixed orthodontic treatment and their association with sagittal tooth movement (STM). Materials and Methods In this study of both arches, 60 periodontally healthy subjects who had completed fixed orthodontic treatment were included. Using pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…A limitation involved in the assessment of gingival margin height is that intraoral photographs did not represent the real size of this variable. Therefore, a lot of studies [ 20 , 23 , 26 ] evaluated gingival modifications including the measurements of clinical crown length (CL) on dental casts. Trentini et al [ 27 ] demonstrated the reliability of photographs and dentals casts for accurate measurements of keratinized tissue width.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation involved in the assessment of gingival margin height is that intraoral photographs did not represent the real size of this variable. Therefore, a lot of studies [ 20 , 23 , 26 ] evaluated gingival modifications including the measurements of clinical crown length (CL) on dental casts. Trentini et al [ 27 ] demonstrated the reliability of photographs and dentals casts for accurate measurements of keratinized tissue width.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival changes are mainly associated not only with the modifications of teeth bucco-lingual inclinations but also with the derotation and extrusive movements obtained during arch expansion, alignment and leveling of the anterior region. In literature, several studies have assessed gingival margin modifications in permanent dentition before and after fixed appliances revealing that some changes of gingival thickness and keratinized gingival width occurred as a consequence of a better teeth position that allows a different gingival architecture [ 19 , 20 ]. However, to our best knowledge no studies evaluated gingival esthetics in mixed dentition after a Phase 1 interceptive treatment performed only by means of CAT.…”
Section: Introductionmentioning
confidence: 99%
“…These results seem optimistic compared to those obtained after classical orthodontic treatment. Indeed, a significant reduction in gingival thickness was demonstrated in the region of the maxillary (by 0.15–0.35 mm) and mandibular (by 0.18–0.3 mm) anterior teeth after their displacement in the sagittal plane [ 50 ]. A mean reduction in the KT height of 0.25 mm immediately after conventional treatment has also been reported [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mean reduction in the KT height of 0.25 mm immediately after conventional treatment has also been reported [ 51 ]. According to other authors, a significant reduction in KT width occurred only in maxillary lateral incisors after protrusive movement, giving rise to the hypothesis that there is a positive relationship between sagittal tooth displacement and KT width [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation